KETIMPANGAN JENDER DALAM AKSES PELAYANAN KESEHATAN RUMAH TANGGA PETANI PEDESAAN: KASUS DUA DESA DI KABUPATEN TEGAL, JAWA TENGAH - JOKO MARIYONO; APRI KUNTARININGSIH; ENNY SUSWATI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
The role of woman in rural and agricultural development is very important because more thana half of work in agriculture and rural areas is carried out by woman labors. Consequently, thewomen ought to have equity in right with men to get health services. But, there is a stronghypothesis that women have less access to health services than men because of social andcultural factors in rural areas. This study aims to examine the gender disparity anddiscrimination of health. The disparity is measured using concentration curve andconcentration index, whereas the discrimination is approached using microeconomic theory ofconsumption. The results of indicate that there is a small difference in health disparitybetween women and men; even women get more portion than men. This is because womenhave specific characteristics in terms of health problem, in which men do not have.